The Influence of The Abraham Accords on the Visual Coverage of the Israeli-Palestinian Conflict in Arab Media: A Comparative Analysis - Alsaba, Mona (AUC Knowledge Fountain, 2023)
This study examines the influence of the official signing of the Abraham Accords on the Arab media visual coverage of the Israeli-Palestinian conflict. This study operationalized visual frames in terms of the human-interest vs technical frame and peace vs war frame, and explored the use of graphic portrayal as a framing device, in order to compare between the Arab media visual framing of the Israeli-Palestinian conflict before and after the official signing of the Abraham Accords to examine the impact of foreign policy on the coverage among news outlets of different Arab countries. A comparative analysis was conducted relying on the collection of visuals from the digital websites of three Arab television stations: Saudi Arabia-government owned Al Arabiya (reflecting a conservative stand towards the normalization), the Qatar-government owned Al Jazeera (reflecting an opposing stand towards the normalization) and Sky News Arabia, co-owned by Abu Dhabi Media Investment Corp, owned by a member of the Abu Dhabi Emirate ruling family, and British Sky Broadcasting (reflecting a supportive stand towards the normalization). The study examined a total of 3,298 visuals from two Gaza wars: the 2014 Gaza war that took place before the signing of the Abraham Accords and the recent Gaza war in 2021 which came after. The results show significant differences between the visual coverage of both wars as well as between the three news websites. This study contributes to the current understanding of how conflicts are framed on multi-levels, where peace vs war frames act as an outline framework reflecting the actual events, followed by more specific frames related to the attributes of war.